The Synonym of Meaning in Acehnese And Indonesian Proverbs: Cognitive Semantic Analysis - Dara Mubshirah; Mulyadi (RETORIKA: Jurnal Ilmu Bahasa, 2023)
Each language has proverbs contain the same meaning, but its own way of using metaphorical elements by the characteristics of society. This study aims to identify Indonesian proverbs and Acehnese proverbs with various metaphors that have the same meaning. This study employs a qualitative methodology and descriptive analysis, which indonesian and Aceh proverbs are the subject of the study. According to their lexical and figurative interpretations, Acehnese and Indonesian proverbs are compared and contrasted using a contrastive analysis as the data analysis technique. The result showed that Acehnese proverbs have the same meaning as Indonesian proverbs. These meanings are categorized into 3 categories, namely (1) Using the same word and the same meaning, ( 2) Using different words but the same context, the same meaning, (3) Using a different words whole (no relation at all).